Training Process in Organization Employee Development Program Implementation - Rustamov, Rustam B.; RzaGuliyeva, Lala R.; Kurnaz, Sefer (International Journal For Research In Business, Management And Accounting, 2017)
There is no doubt that development of company depends on how to develop its main potential – employees. It is obvious that only highly qualified staff will be able to take the company to a leading position in servicing sphere, leaving the competitors far behind. The system of personnel training and development forms help and support, increase the professional skills of employees, provide them with modern economic thinking and teamwork. The productivity and efficient operation of the enterprise as a whole increases through the process of learning and continuously improvement. This paper describes importance of training process in engineering companies and leading place of training center with philosophy of learning organization.